Temporal Decline in Pathogen-Mediated Release of Methyl Salicylate Associated With Decreasing Vector Preference for Infected Over Uninfected Plants - Martini, Xavier; Coy, Monique; Kuhns, Emily; Stelinski, Lukasz L. (Frontiers in Ecology and Evolution, 2018)
Asian citrus psyllid Diaphorina citri Kuwayama is the vector of the phytopathogenic bacteria Candidatus Liberibacter asiaticus (CLas). D. citri is attracted to methyl salicylate (MeSA) that is emitted by CLas-infected citrus. MeSA is catalyzed from salicylic acid (SA) by salicylic acid methyl transferase (SAMT). In addition, salicylate hydroxylase, an enzyme that degrades SA and suppresses host plant defense, is unregulated in CLas-infected as compared with uninfected citrus. Based on these findings, we hypothesized that CLas-induced plant volatile emissions and SAMT expression may decrease over time following CLas infection. We first identified the putative Citrus sinensis SAMT (CsSAMT) that methylates SA to MeSA. Thereafter we compared MeSA emission and SAMT expression between uninfected citrus, citrus recently (< 6 months) infected with CLas, and old (> 1year) CLas-infected citrus. We found that MeSA emission increased in citrus recently infected with CLas, whereas both MeSA emissions and SAMT expression decreased in long-infected citrus. In behavioral assays, D. citri preferred settling in asymptomatic citrus recently infected with CLas rather than on uninfected citrus trees or long-infected trees. We conducted olfactometer assays that showed that the odor of citrus recently infected with CLas was more attractive to psyllid than the odor of uninfected citrus of long-infected trees. We linked the preference for citrus odor recently infected with CLas to the increase of MeSA emission following CLas infection. Overall, our study demonstrated pulsed changes in citrus odor following CLas infection. These changes affected the behavior of the CLas vector. Our study confirms previous reports demonstrating that plant defenses boosted following phytopatogen infection tend to decrease over time. Implications on the CLas epidemic are discussed.